Analysis of contemporary HIV/AIDS health care costs in Germany: Driving factors and distribution across antiretroviral therapy lines. Issue 26 (June 2016) - Treskova, Marina; Kuhlmann, Alexander; Bogner, Johannes; Hower, Martin; Heiken, Hans; Stellbrink, Hans-Jürgen; Mahlich, Jörg; Schulenburg, Johann-Matthias Graf von der; Stoll, Matthias
Abstract : Abstract: To analyze contemporary costs of HIV health care and the cost distribution across lines of combination antiretroviral therapy (cART). To identify variations in expenditures with patient characteristics and to identify main cost determinants. To compute cost ratios between patients with varying characteristics. Empirical data on costs are collected in Germany within a 2-year prospective observational noninterventional multicenter study. The database contains information for 1154 HIV-infected patients from 8 medical centers. Means and standard deviations of the total costs are estimated for each cost fraction and across cART lines and regimens. The costs are regressed against various patient characteristics using a generalized linear model. Relative costs are calculated using the resultant coefficients. The average annual total costs (SD) per patient are [Euro sign]22, 231.03 (8786.13) with a maximum of [Euro sign]83, 970. cART medication is the major cost fraction (83.8%) with a mean of [Euro sign]18, 688.62 (5289.48). The major cost-driving factors are cART regimen, CD4-T cell count, cART drug resistance, and concomitant diseases. Viral load, pathology tests, and demographics have no significant impact. Standard non-nucleoside reverse transcriptase inhibitor-based regimens induce 28% lower total costs compared with standard PI/r regimens. Resistance to 3 or more antiretroviral classes induces a significant increase in costs. HIV treatment in Germany continues to be expensive. Majority of costs are attributable to cART. Main cost determinants are CD4-T cells count, comorbidity, genotypic antiviral resistance, and therapy regimen. Combinations of characteristics associated with higher expenditures enhance the increasing effect on the costs and induce high cost cases. Abstract : Supplemental Digital Content is available in the text